6(y-1)-9=-5(-3y+5)-3y
6y-6-9=15y-25-3y
6y-15=12y-25
+15. +15
6y=12y-25
+12y +12y
18y=-25
÷18. ÷18
y=-1.38
or -1 19/50
Answer:99°
Step-by-step explanation:
180-123=57
x=57+42
x=99°
Midpoint formula : (x1 + x2) / 2, (y1 + y2) / 2
(2,6)...x1 = 2 and y1 = 6
(x,y)...x2 = x and y2 = y
sub
(2 + x) / 2, (6 + y) / 2 = (4,10)
(2 + x) / 2 = 4
2 + x = 4 * 2
2 + x = 8
x = 8 - 2
x = 6
(6 + y)/2 = 10
6 + y = 10 * 2
6 + y = 20
y = 20 - 6
y = 14
so ur other endpoint is (6,14) <==
Answer:
The correct answer is option B.
(4x + 8)/(5x - 5)
Step-by-step explanation:
It is given an expression in variable x
2x/(x - 1) ÷ 5x/(2x + 4)
<u>To find the correct option</u>
2x/(x - 1) ÷ 5x(2x + 4) = 2x/(x - 1) * (2x + 4)/5x
= 2x/(x - 1) * 2(x +2)/5x
= [2x * 2 * (x + 2)]/[(x - 1)5x]
= 4(x +2)/5(x - 1)
= 4x + 8)/(5x - 5)
The correct answer is option B.
(4x + 8)/(5x - 5)
Answer:
B 0.6825
Step-by-step explanation:
From the tables
0.80 = 02881 of the area
1.25 = 0.3944 of the area
Sum of these 2 = 0.6825